Respuesta :
Answer:
a=-1
Step-by-step explanation:
we need to get a by itself
first combine like terms
12+16a=-4
now we need to get rid of the 12 so subtract it to other side
-16=16a
now divide 16 by -16 which gives you -1=a
Answer: a=-1
12+12a+4a=-4
(Collect like terms)
12+16a=-4
(Move constant to the right-hand side and change it’s sign)
16a=-4-12
(Calculate the difference)
16a=-16
(Divide both sides of the equation by 16)
a=-1
12+12a+4a=-4
(Collect like terms)
12+16a=-4
(Move constant to the right-hand side and change it’s sign)
16a=-4-12
(Calculate the difference)
16a=-16
(Divide both sides of the equation by 16)
a=-1